Fish Plaza as a Centre of Fisheries Product Trading in Tuban Regency, East Java - Yuyun Suprapti; Miftachul Munir; Muhammad Zainuddin (Jurusan Perikanan dan Kelautan, 2020)
The purpose of this research is to find out how Plaza Ikan encourages fish traders to increase their business. One of the efforts of the Tuban Regency Government to increase the added value of fish products is to establish a fish Plaza. The fish plaza is an integrated fish auction place that is packaged in a modern way and integrates with the sale of fresh fish, smoked fish and various processed fish. With the concept of integration, it is hoped that the economy of Tuban fishermen will improve. The research method used a qualitative descriptive method, while the data collection using interviews and questionnaire techniques. Of the 30 respondents who answered everyday trading at the fish plaza, 20 respondents strongly agreed, 7 respondents agreed and 3 respondents were doubtful. A comfortable place to sell, 17 respondents strongly agree, 8 respondents agree, 3 respondents doubt, 2 respondents disagree. Profits are increasing, 5 respondents disagreed, 25 respondents strongly disagreed. The consumers are many and varied, 12 respondents strongly agree, 5 respondents agree, 3 respondents doubt, 4 respondents disagree, 6 respondents strongly disagree